Indonesia-China Trade Performance in the RCEP Forum - Abdullah, Ragimun; Mutaqin; R. Nurhidayat; Yasin, Akhmad (Journal of Economics and Behavioral Studies, 2022)
This study aims to map out Indonesia’s export performance, the competitiveness of its commodities, and the position of some of Indonesia’s flagship commodities in China. The research method used in this study is the Revealed Comparative Advantage (RCA) and the Constant Market Share Analysis (CMSA). The data is from the Indonesia Central Statistics Agency (BPS) and UN Comtrade for 4-digit HS products. The finding from this study indicates that Indonesia’s trade balance with China for the last three years (2018-2020) has widened the deficit. Intense negotiations with China are necessary to open up trade access to overcome the trade deficit. The Government is encouraged to launch the development of flagship products with high market values, such as chemicals, machinery, electricity, and textiles. In addition, the national downstream program for mineral and metal products is encouraged to do more robust plans, including considering attracting new industrial investment from China.